Unsur Intrinsik dan Sosiologi Sastra dalam Cerpen Blabur Ring Pasisi Sanur Karya Carma Mira - Ni Komang Ayuk Lilis Saputri; Gusti Nyoman Mastini; A.A Made Putra Arsana (Dharma Acariya Nusantara Jurnal Pendidikan Bahasa dan Budaya, 2026)
This study examines the short story Blabur ring Pasisi Sanur as a literary work that represents the social reality of Balinese society. The formulation of research problems includes the analysis of intrinsic and extrinsic elements with a literary sociology approach. Robert Stanton's structuralism theory is used to identify intrinsic elements, while Wallek and Warren's theory of literary sociology is used to examine the social aspects contained in short stories. The data collection method is carried out through library studies, interviews, and documentation, with qualitative descriptive analysis through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the intrinsic elements of short stories include incidents, plots, characters, and settings that form the narrative structure. Meanwhile, the extrinsic element in the form of literary sociology includes three dimensions: (1) the sociology of the author, which highlights the biography and authorship history; (2) the sociology of readers, which emphasizes the responses, assessments, and influences of the work on readers; and (3) the sociology of works, which reflect the socio-religious, social-educational, socio-economic, social, community, and socio-cultural aspects. This study concludes that the short story Blabur ring Pasisi Sanur not only has structural strength in intrinsic elements, but also significant social relevance through the perspective of literary sociology, so it is important as a reflection of the life of the Balinese people.